توظيف التأصيل الإسلامي لعلم النفس في تدريس مقررات علم النفس - عبد الله بن ناصر الصبيح (International Institute of Islamic Thought, 2011)
يناقش البحث توظيف التأصيل الإسلامي في تدريس مقررات علم النفس، من خلال الربط بين المفاهيم الإسلامية والأدلة من القرآن والسنة من جهة، ومفاهيم علم النفس وتطبيقاته من جهة أخرى. وقد تناول الموضوع من خلال أربعة محاور هي: شخصية المدرس، ومصادر المعرفة، وتوظيف القرآن والسنة، وصياغة قواعد وتوجيهات عامة. وقد تضمن البحث وصفاً لبعض المعيقات التي تواجه التوظيف الأمثل للتأصيل الإسلامي في علم النفس. The paper discusses how to apply Islamic perspectives in teaching psychology courses by incorporating Islamic concepts conveyed in the Qur'an and Sunnah with concepts and practices in contemporary psychology. It deals with the topic through four key points: teacher personality, sources of knowledge, applying psychological concepts within Qur'an and Sunnah, and formulating rules and guidelines for an Islamic Psychology. The paper also identifies obstacles facing this effort.